A Descriptive Account on the Accomplishments and the Failures of US Foreign Policy: Korea 1950-1953 - Chaib, Ahmed Karim; Seddiki, Mohammed Cherif (University of Ammar Theledji -Laghouat, 2020)
Since the turn of the twentieth century, the American foreign policy has driven a rising interest on several topics. The swing from total isolationism to direct interventionism was a significant event that requires consideration. From this point onward, the United States foreign policy played a major role on the international scene. Eventually, the end of WWП and the outbreak of the Cold War was the emergence of the U.S. alongside the Soviet Union as superpowers competing to dominate the globe. This led to military confrontation starting with the Korean War 1950-1953 to escalation in other parts of the world. The concern of this paper is to exhibit the type of the American foreign policy toward the Soviet Union after 1945 during the Korean War. The latter was a battleground that gathered the two superpowers. In particular, the U.S. aim behind the intervention was the containment of the communist spread in the Peninsula and eventually reunify it under friendly government. Thus, one would wonder: did the U.S. achieve its ultimate goal? Was the intervention justified? To what extent was the American intervention a success for the goals set? Through a descriptive and analytical approach, this work attempts to contemplate the U.S foreign policy in the first years of the Cold War and particularly in the Korean War. Furthermore, this work explains how effective the American intervention was in containing Communism. Therefore, it is to be concluded that, though incomplete, the success of such intervention was significant. Overall, this work analyzes, examines, and hence evaluates the U.S. foreign policies towards Korea during the war (1950-1953). It does, as well, provide a ground floor for some future studies on the troubled U.S and North Korean relations during and after the Cold War